PENYULUHAN GIZI DAN PEMBERIAN TABLET BESI TERHADAP PENGETAHUAN DAN KADAR HEMOGLOBIN SISWI SEKOLAH MENENGAH ATAS NEGERI DI MAMUJU - Ahmady Ahmady; Hapzah Hapzah; Dina Mariana (Politeknik Kesehatan Kemenkes Mamuju, 2016)
The prevalence of anemia in adolescent girls junior and senior high school in Mamuju is 27%. This study to determine the effect of nutritional counseling and suplementation iron tablets to knowledge and hemoglobin ( Hb ) status of senior high school student in West Sulawesi. This type of research is a quasi-experimental design using non- randomized control group pretest-posttest. Samples of the intervention group were 30 students and a control group of 30 students. Student knowledge was measured using questionnaires and hemoglobin concentration using hemoglobinometer. Analysis using Wilcoxon Test, Paired Sample T-Test and Independent T Test. The results showed the results of this study showed no difference in the increase in knowledge after counseling, while the suplementation of iron tablets contained elevated levels of hemoglobin